2012
DOI: 10.5483/bmbrep.2012.45.4.242
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and piperine enhance radiosensitivity of tumor cells

Abstract: The use of ionizing radiation (IR) is essential for treating many human cancers. However, radioresistance markedly impairs the efficacy of tumor radiotherapy. IR enhances the production of reactive oxygen species (ROS) in a variety of cells which are determinant components in the induction of apoptosis. Much interest has developed to augment the effect of radiation in tumors by combining it with radiosensitizers to improve the therapeutic ratio. In the current study, the radiosensitizing effects of resveratrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…It was also reported that sequential treatment of SW1 cells first by IR to increase surface expression of TRAIL-R, and then 16h after irradiation with RSV for an additional 24h to induce endogenous TRAIL translocation to the cell surface, and to suppress anti-apoptotic cFLIP and Bcl-xL, resulted in strong upregulation of RV-induced apoptosis and dramatic downregulation of SW1 clonogenic survival. This observation on the radiosensitizing effects of RSV on apoptosis was supported by another study in mouse melanoma B16F10 cells (Tak et al, 2012). It was found here that RSV (0, 10, 20 µM) enhanced the radiation (5Gy; dose rate of 1Gy/min)-induced apoptotic induction higher than IR or RSV alone under similar conditions.…”
Section: Skin Cancersupporting
confidence: 84%
See 2 more Smart Citations
“…It was also reported that sequential treatment of SW1 cells first by IR to increase surface expression of TRAIL-R, and then 16h after irradiation with RSV for an additional 24h to induce endogenous TRAIL translocation to the cell surface, and to suppress anti-apoptotic cFLIP and Bcl-xL, resulted in strong upregulation of RV-induced apoptosis and dramatic downregulation of SW1 clonogenic survival. This observation on the radiosensitizing effects of RSV on apoptosis was supported by another study in mouse melanoma B16F10 cells (Tak et al, 2012). It was found here that RSV (0, 10, 20 µM) enhanced the radiation (5Gy; dose rate of 1Gy/min)-induced apoptotic induction higher than IR or RSV alone under similar conditions.…”
Section: Skin Cancersupporting
confidence: 84%
“…Its role becomes critical since reduction in radiation-induced ROS generation by plant-derived compound, conferring protection to normal cells have been reported (Lee et al, 2010). More importantly, in the colon carcinoma study (Tak et al, 2012), increase in the ROS have been shown to contribute to decrease in cancer cell viability. Therefore, ROS role warrants further investigation in different models of cancers using combine RSV+IR treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…73 Resveratrol additionally has demonstrated radiosensitizing behavior in other cancer cells. 74 Therefore, polyphenols could potentially augment traditional cancer therapy while minimizing radiation-induced skin toxicity. In addition to requiring further studies regarding their interaction with tumor cells, more rigorous standardization of polyphenol processing is needed to demonstrate which particular molecules will have the greatest efficacy.…”
Section: Polyphenolsmentioning
confidence: 99%
“…There are two excitation wavelengths. At low values of MMP, JC-1 remains a monomer (FL-1, green fluorescence; 527 nm) whereas it forms aggregates at high MMP (FL-2, red fluorescence; 590 nm) according to the recommended procedure (20). Cells were trypsinized, the cell pellets were resuspended in PBS, and incubated with 10 µM JC-1 for 30 min at 37˚C.…”
Section: Measurement Of Mmp (δψ M )mentioning
confidence: 99%